Upaya Meningkatkan Prestasi Belajar Menulis Teks Pidato Melalui Metode Kolaborasi - Suramto Tri Widodo (Nusantara: Jurnal Pendidikan Indonesia, 2021)
This study aims to improve the learning achievement of writing speech texts in Class VI Semester II SDN Kratonan No. 3 Surakarta Academic Year 2019/2020, which corresponds to Indonesian language learning on theme 7: Leadership; Sub Theme 1: Leaders Around Me on KI. 4.3 "Writing private speeches using standard vocabulary and effective sentences as a form of self-expression.". This type of research is Classroom Action Research (PTK). With a length of research for 4 (four) months starting January to April 2020. This study's subjects were students of Class VI SDN Kratonan No. 3 Surakarta, totaling 29 students. Data collection techniques used interviews, observation, test methods, performance, and documentation. The results showed that applying the collaboration method could improve the sixth-grade students' writing skills of SDN Kratonan No.3 Surakarta Academic Year 2019/2020.